A landscape manifesto - Balmori, Diana; Conan, Michel (New Haven : Yale University Press, 2010)
Makes the case for landscape as an art. This book presents the author's most complete vision yet of the theory and practice of urban landscape design as a discipline that combines the science of ecology with the formal aspects of aesthetics. It also includes discussions of urban ecology, and environmentally beneficial building techniques.
"Supported by a grant from the Graham Foundation for Advanced Studies in the Fine Arts."--T.p. verso.
Includes bibliographical references and index.
boek
Keywords: Balmori, Diana; Landscape architecture; Landscape architecture -- Designs and plans